Supply Chain Connectivity: Enhancing Participation in the Global Supply Chain - Epictetus E. Patalinghug (Philippine Institute for Development Studies (PIDS), 2015)
Supply chain connectivity is vital for the efficient flow of trade among APEC economies. This paper reviews the literature and supply chain management, describes the barriers to enhancing participation in global supply chain, analyzes the various measures of supply chain performance, and suggests steps for the Philippines to fully reap the benefits of the global value chain.
Keywords: 330; APEC; transportation; supply chain connectivity; global supply chain